Research Trends in Module Development Based on Local Wisdom in Elementary Schools: Bibliometric Analysis of Selected Journals 2015-2025 - Fatwa, Ayomi; Tri Joko Raharjo; Bambang Subali; Ellianawati Ellianawati (Journal of Primary Education, 2024)
This study analyzes the trend of local wisdom-based module development in elementary schools (SD) during 2015-2025 with a bibliometric approach. Using scientific databases such as Google Scholar, Crossref, and Open Alex and the Publish or Perish (PoP) application, 46 relevant documents were obtained from 2,136 documents. Bibliometric analysis with VOSviewer mapped topic relationships, theme clustering, and research trends. The focus of the study includes the integration of local wisdom values in elementary school curriculum and learning, annual publications, topics, methodology, and the origin of local wisdom. The results show the dominance of the theme of local wisdom integration nationally, while the representation of certain regions is still minimal. Key findings include improved student understanding and learning outcomes, but numeracy, literacy, and creativity are less studied. This study found gaps in local wisdom-based digital innovation, contextual exploration, and module effectiveness evaluation. It is suggested that future research focus on technology integration, local wisdom variation, and a holistic approach in developing local wisdom-based learning modules.